Assessing the influence of observations on the generalization performance of the kernel Fisher discriminant classifier - Lamont, Morné Michael Connell (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Statistics and Actuarial Science))—Stellenbosch University, 2008.